Eunice and Kate - Llanos, Mariana (Penny Candy Books, 2020)
"Eunice and Kate live with their moms next door to each other in the heart of the city and have a lot in common--even though they have different dreams for the future: Kate wants to be an astronaut and Eunice wants to be a ballet dancer. But when they draw portraits of each other in art class, things get mixed up. Eunice draws Kate as a ballet dancer and Kate draws Eunice as an astronaut, and they both get more than a little annoyed. Can their friendship survive? With a little help from their moms, the girls come to learn the value of respecting each other's different dreams"--Publisher's website.